2017
DOI: 10.7307/ptt.v29i3.2152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Horizontal Curves and Percentage of Heavy Vehicles on Right Lane Capacity at Multi-lane Highways

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Estimated capacities were found to differ significantly between the distressed and un-distressed sections. Semeida and El-Shabrawy [1] explored how pavement distresses, pavement roughness, and longitudinal grade affect the operating speed (V 85 ) of traffic on multi-lane roads in Egypt. Using linear regression, it was found that V 85 increased with an increase in the PCI, and it was also concluded that IRI is an effective factor on speed reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated capacities were found to differ significantly between the distressed and un-distressed sections. Semeida and El-Shabrawy [1] explored how pavement distresses, pavement roughness, and longitudinal grade affect the operating speed (V 85 ) of traffic on multi-lane roads in Egypt. Using linear regression, it was found that V 85 increased with an increase in the PCI, and it was also concluded that IRI is an effective factor on speed reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because traffic is a significant controlling parameter on multilane highways, the analysis of traffic flow in terms of flow, speed, and density is necessary. Traffic speed is significant because it influences safety, time, and economics, and it may also be an accurate indicator of pavement condition of roadway facilities [1]. In the planning, estimating, and understanding of road capacity, traffic flow characteristics are essential [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, traffic volume composition is also significantly associated with highway capacity on open-access highways, especially in developing countries such as India and Sri Lanka [3,24]. Researchers also studied the impact of pavement condition on free-flow speed but only for controlledaccess and partially controlled-access highways [25,26]. Another study by Salini and George [2] concluded that the buses stopping at bus stops also obstruct traffic flow on openaccess multilane highways in India.…”
Section: Synthesis Of Past Literaturementioning
confidence: 99%
“…The authors found that factors, such as a high number of pedestrians, bicycles, and vehicle traffic flow, significantly reduced the mean speed on urban roads. Semeida and El-Shabrawy [25] explored the influence of pavement condition, roughness, and longitudinal grade on passenger car operating speed (V85) using three different modeling approaches and identified international roughness index (IRI) as the most critical parameter. Wang [60] developed a relationship between the drivers' speed and the road environment on partially controlledaccess highways.…”
Section: Synthesis Of Past Literaturementioning
confidence: 99%
“…Comparison charts were provided with help of CA model for car following car condition and car following truck condition which showed the amount of change occurred due to presence of truck and same study was carried out for different percentage of trucks and it was found that higher percentage of trucks results in higher impact. Semeida (2017) have shown impact of HV in terms of capacity loss that occurred due to various percentage of heavy vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%